2019
DOI: 10.1186/s12889-019-7911-x
|View full text |Cite
|
Sign up to set email alerts
|

A health care labyrinth: perspectives of caregivers on the journey to accessing timely cancer diagnosis and treatment for children in India

Abstract: BackgroundCure rates for children with cancer in India lag behind that of high-income countries. Various disease, treatment and socio-economic related factors contribute to this gap including barriers in timely access of diagnostic and therapeutic care. This study investigated barriers to accessing care from symptom onset to beginning of treatment, from perspectives of caregivers of children with cancer in India.MethodsSemi-structured in-depth interviews were conducted with caregivers of children (< 18 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 30 publications
5
22
0
Order By: Relevance
“…relational and social beliefs of families, limited knowledge and awareness of the disease and health system and financial problems). These barriers were similar to those identified in previous literature [ 33 , 34 , 38 41 ], including the qualitative study on caregiver perspectives [ 35 ]. While this is important, the studies did not illuminate how these barriers are perceived and what influences these perceptions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…relational and social beliefs of families, limited knowledge and awareness of the disease and health system and financial problems). These barriers were similar to those identified in previous literature [ 33 , 34 , 38 41 ], including the qualitative study on caregiver perspectives [ 35 ]. While this is important, the studies did not illuminate how these barriers are perceived and what influences these perceptions.…”
Section: Discussionsupporting
confidence: 86%
“…A similar qualitative study on barriers to accessing childhood cancer care from the perspective of caregivers was conducted by the lead study investigator and team [ 35 ]. The results indicated that time to definitive diagnosis and treatment, social supportive care and ongoing emotional and financial impacts were the major themes affecting access to cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that delay occurs at different stages during diagnostic pathways due to a variety of factors [ 8 11 , 30 32 ]. This is in line with our findings as the pathway to diagnosis was shaped by factors related to disease, patient/parents and the HCS.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, these policies give rise to the differential experiences of populations occupying ‘specific social locations such as social class, gender, age, and race’ [( Raphael and Bryant, 2019 ), p. 61]. Social locations are complex and intersecting, created by the identities that any person, group, or community occupies in relation to others ( Crenshaw, 1997 ; Nixon, 2019 ). Civil society, corporate sectors, organized labor, along with ideological and economic systems, all influence political systems though multiple pathways that direct distributive policies ( Raphael and Bryant, 2019 ).…”
Section: Power Political Economy and Pandemicmentioning
confidence: 99%